2017
DOI: 10.1097/igc.0000000000001087
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Primary Cell Culture From Ascitic Fluid and Solid Tumor Obtained From Epithelial Ovarian Carcinoma Patients

Abstract: This study highlights the fact that establishing primary cultures from ascitic fluid or solid tumor tissue may help us to understand the molecular profile of the cancer cells, which allow us to select the best chemotherapeutic agent for ovarian cancer patients and thus take a step toward patient-tailored therapy so that patients are not exposed to drugs to which they are not likely to respond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…The maintenance of the characteristics of tumor cells in a multicellular organization, to mimic the spheroids observed in the ascitic fluids of ovarian carcinoma patients, is made particularly complicated by the alteration of the cellular response due to the freezing procedure and culture passage [20,21]. The literature data reported the successful creation of several ovarian carcinoma cell lines [20,22,23], although often not taking into account the essential role of spheroids in ovarian cancer progression. It is necessary to bear in mind that established cell lines are an in vitro simplification of the tumor microenvironment and that heterogeneity is observed.…”
Section: Discussionmentioning
confidence: 99%
“…The maintenance of the characteristics of tumor cells in a multicellular organization, to mimic the spheroids observed in the ascitic fluids of ovarian carcinoma patients, is made particularly complicated by the alteration of the cellular response due to the freezing procedure and culture passage [20,21]. The literature data reported the successful creation of several ovarian carcinoma cell lines [20,22,23], although often not taking into account the essential role of spheroids in ovarian cancer progression. It is necessary to bear in mind that established cell lines are an in vitro simplification of the tumor microenvironment and that heterogeneity is observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, the majority of patients eventually become resistant to chemotherapeutic drugs and this causes the prognosis of these patients to be unsatisfactory ( 20 ). Previous studies for ovarian cancer were primarily based on cells generated from primary lesions ( 21 , 22 ), and few of these studies focused on the omentum ( 23 ). It has been suggested that metastatic cancer is a markedly heterogeneous disease at the genetic, transcriptomic and microenvironment levels ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Qiu X et.al разработали микрофлюидное устройство, позволяющее проводить более мягкую механическую дезагрегацию клеток, используя сеть каналов и «гидродинамические скальпели» [21]. В исследовании Kar et.al успешно получали первичные клеточные линии рака яичника как с помощью механической диссоциации ткани, так и ферментативно с помощью Dispase II [22].…”
Section: механическая диссоциацияunclassified